Adaptación del modelo 5E con el uso de herramientas digitales para la educación: propuesta para el docente de ciencias - Bastida Izaguirre, Dafne Bastida (Revista Científica, 2019)
This article presents the design and application of a teacher training workshop for science university professors based on the Model 5E in combination with the use of digital tools. The purpose is to develop the skills to design and implement strategies and didactic resources that enable the integration of the model and Information and Communication Technologies that allows the science teacher to innovate in the classroom. The workshop consists of three sessions where the steps are reviewed to engage, explore, explain, elaborate and evaluate through activities that have a participatory approach and where much of the collaborative work is encouraged. The workshop was held at the University Center of Biological and Agricultural Sciences of the University of Guadalajara where 14 teachers from the area of cell biology participated. The response to the workshop by the participants was satisfactory as it allowed them to reflect on their practice, to have greater openness and to lose the fear of using technologies, as well as consider the 5E model as a very important strategy for its students to achieve meaningful learning.